Risk-mitigation for projects that rely on genetic resources from multiple sources: a project planner’s decision-making tool - López Noriega, Isabel; Halewood, Michael (2021)
The purpose of this decision-making tool, is to help research and development (R&D) project planners mitigate the risk of project setbacks or failures, as a result of not being able to access genetic resources and related research inputs, to use them as needed for project purposes, or to disseminate research products derived from their use. It is intended primarily for planners of projects that rely on accessing, pooling and sharing a diverse portfolio of genetic resources from multiple sources in different countries and continents; projects for which the risks are substantially increased, in proportion to the diversity and number of sources of genetic resources they rely upon.